2018
DOI: 10.3390/en11061416
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Charging of Electric Vehicles with Trading on the Intraday Electricity Market

Abstract: Trading on the energy market is a possible way to reduce the electricity costs of charging electric vehicles at public charging stations. In many European countries, it is possible to trade electricity until shortly before the period of delivery on so called intraday electricity markets. In the present work, the potential for reducing the electricity costs by trading on the intraday market is investigated using the example of the German market. Based on simulations, the authors reveal that by optimizing the ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 23 publications
(20 reference statements)
0
13
0
Order By: Relevance
“…Smart charging [10], which allows the control of charging processes in a coordinated way, is often seen as an important step towards a successful grid integration of EVs and a profitable operation of public EV charging stations. Different approaches towards increasing the grid stability [11,12] and the profit of EV charging station operators [13][14][15] are proposed in the literature. Smart charging could be also applied by individual users in order to reduce their charging costs [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Smart charging [10], which allows the control of charging processes in a coordinated way, is often seen as an important step towards a successful grid integration of EVs and a profitable operation of public EV charging stations. Different approaches towards increasing the grid stability [11,12] and the profit of EV charging station operators [13][14][15] are proposed in the literature. Smart charging could be also applied by individual users in order to reduce their charging costs [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…However, in the real life scenario it can only takes place with aggregator because of bidding size capabilities and advantage of large pooling. Approach similar to the study has been found in the literature where trading of electricity is done in two stage, where in first stage,electricity is traded on day-ahead market based on historical driving and charging pattern [37]. In the second stage, deviations from the prediction can be adjusted on intra-day market.…”
Section: Limitationsmentioning
confidence: 98%
“…It is possible to trade before 5-minutes of delivery on IDM in the Netherlands. Such approach is practical and legal, moreover, several studies have also explored it for different countries in Europe [37,45]. Based on this approach further modelling assumptions and simplifications will be made in this research.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In a smart grid environment, smart charging provides flexibility to the grid, allowing demand response services. Smart charging strategies have been used in [21] by comparing different strategies with the aim of providing frequency regulation services, in [45] in conjunction with the provision of vehicle-originating signals to minimise the variability of the aggregate power pattern with respect to a predefined reference, in [55] to minimise the cost of the charging schedule by taking into account the trading on the intraday electricity market. From a technical point of view, the implementation of dynamic EV charging is discussed in [56] considering different solutions for AC charging, Chademo and Combined Charging System (CCS)/COMBO.…”
Section: Evappmentioning
confidence: 99%